Strategi Pemberdayaan Masyarakat Berbasis Institusi Lokal dalam Penanganan Kemiskinan Pedesaan (Kasus Implementasi Program Pembangunan Sosial Masyarakat Berbasis Gampoeng oleh BRR di Desa Kuta Glumpang Kecamatan Samudera Kabupaten Aceh Utara) - -, Suadi (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
: The objective of research is to describe community empowerment in recovering poverty based on local institution which is different from others in rehabilitation and reconstruction Aceh post Tsunami. This research is focused on implementation program and the result of outreach program. The research has done by used the qualitative-descriptive approach. The data was collected by observation, interview and documentation. Then these data would be analyzed by using interactive analysis model. The result of the research is BRR (Badan Rekonstruksi dan Rehabilitasi) although has placed the facilitator in order to work live-in within two empowerment programs (Revolving Fund and Based Asset Economic Development) but it was not successful in reducing the village poverty. It meant the society has not developed after getting funds which given to them, the revolved fund is not returned in according to the agreement. The society still has mentally consumptive which was higher then productive mental. The revolved fund was used only for the self consumption. Meanwhile the Based Asset Economic Development, the community request from Micro Finance Institution to distribute for concerned community after the facilitator no more incharged in the village. Keywords: Empowerment Strategy, Society, poverty, village.